2007
DOI: 10.2298/sarh0704135z
|View full text |Cite
|
Sign up to set email alerts
|

The influence of respiratory pattern on heart rate variability analysis in heart failure

Abstract: These data suggest that SDB increases HRV both in healthy and heart failure patients; the highest increment is in LF range. Differences in spectral profile of HRV between healthy controls and heart failure patients become more profound during SDB. Controlled respiration during HRV analysis might increase sensitivity and reliability in detection of autonomic dysfunction in heart failure patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Because we assessed the autonomic nervous activity using the average values of HF and LF/HF recorded during HD, total power spectra of HF and LF/HF are considered to increase during the HD to maintain the hemodynamically stable condition. Previous study has also demonstrated significant increase in HF cooperated with the elevation of LF/HF in some condition such as deep and slow breathing as a result of the modulation in autonomic nervous system (18). Furthermore, entropy was significantly increased during HD as compared with the baseline in the non‐hypotension group, and also significantly higher in the non‐hypotension group than in the hypotension group.…”
Section: Discussionmentioning
confidence: 68%
“…Because we assessed the autonomic nervous activity using the average values of HF and LF/HF recorded during HD, total power spectra of HF and LF/HF are considered to increase during the HD to maintain the hemodynamically stable condition. Previous study has also demonstrated significant increase in HF cooperated with the elevation of LF/HF in some condition such as deep and slow breathing as a result of the modulation in autonomic nervous system (18). Furthermore, entropy was significantly increased during HD as compared with the baseline in the non‐hypotension group, and also significantly higher in the non‐hypotension group than in the hypotension group.…”
Section: Discussionmentioning
confidence: 68%